Consumers perception & satisfaction towards Islamic banking (case study of MBB, RHB & KFH Bank) / Emmy Marina Marzuki - Marzuki, Emmy Marina (2011)
This chapter introduces the research outline of the study, which illustrates the background, problem statement, research objectives and questions, significance of the study, definition ofterms, literature review and research methodology.